Analisa Dan Perancangan Sistem Pakar Identifikasi Penyakit Diabetes Pada Remaja Dengan Metode Fuzzy Berbasis Website - Hatta Agus Hairul; Hidayatullah Al Islami (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
At this time many teenagers are at risk of diabetes, according to data from IDAI (Ikatan Dokter Anak Indonesia) which states that the number of diabetes that occurs in children and adolescents in Indonesia in the age range 0-18 years has increased by 700% in a period of 10 years. From September 2009 to September 2018 there were 1213 cases of diabetes in children and adolescents. To overcome this problem, an Expert System is needed to identify diabetes based on a website using the fuzzy method as a source of information and as an alternative to consult so that the risk of diabetes can be known from an early age so that can reduce the number of diabetics. The Tsukamoto fuzzy method was chosen because it has a fairly high level of accuracy and is easy to apply. In his inference, the Tsukamoto method has several stages, namely: fuzzification, formation of a knowledge base or rules, inference engine, and defuzzification. In determining the identification of diabetes risk, it is determined based on 4 input variables, namely: medical history, diet, lifestyle, and understanding and health checks. Each variable has several questions, each question has several choices where each choice has a weighted value. The data was obtained from interviews with doctors and based on related literature studies. This research can make it easier to determine the results of diabetes risk decisions in adolescents and get solutions for handling and preventing them with an accuracy rate of 81.5%.